Patient-centric ICTs based healthcare for students with learning, physical and/or sensory disabilities. Issue 4 (July 2018) - Papanastasiou, George; Drigas, Athanasios; Skianis, Charalabos; Lytras, Miltiadis; Papanastasiou, Effrosyni
Highlights: Patient centric ICTs based healthcare improves quality of care and life. Customized informatics increase independence and recognize individuality. Students with disabilities can control flexible and responsive healthcare services. Outcomes lead to less problem behaviors and qualitative education. Professionals better understand the communication needs of disabled students. Abstract: The purpose of this review article is to explore a new paradigm on healthcare assessment and intervention practices for students with learning, physical and/or sensory disabilities. The perspective presented here is regarded as patient centric and relies on ICTs, in order to address evidence–based treatment and care, meeting every individual's health profile, with regard to his or her needs, preferences, goals and culture. Patient-centric ICTs based approach has an impact on healthcare systems, introducing a multi-disciplinary care planning that overcomes individual, professional and organizational barriers, reduces anxiety and establishes better understanding with the student at the center. Generally, results show the impact of the interoperability of healthcare information between patients' healthcare record and information systems which facilitate healthcare systems to be lifesaving if available at the time of medical examination. When medical treatment is combined with ICTs based methods and applications such as Serious Games, Mobile Assistive Technologies applications, Telehealth Systems and Virtual Training, patients with learning, physical and/or sensory disabilities can benefit from a cost-effective and flexible network model while having their customized needs fully examined and resolved. The articles presented within this review demonstrate that ICTs based patient-centeredness for students with learning, physical and/or sensory disabilities is associated with better (functional) outcomes leading to quality of life and inclusion, improved quality of care, fewer problem behaviors, higher levels of health-related autonomy and greater patient satisfaction.